Gonad Quality of Banana Shrimp Male Broodstock Penaeus merguiensis (De Man, 1888) Fed Different Natural Diets - Nurul Amirah Matmor; Hidayah Manan; Nor Azman Kasan; Mohamad Jalilah; Adnan Amin-Safwan; Mhd Ikhwanuddin (Tropical Life Sciences Research, 2022)
A study was carried out to determine the maturation period, quality and quantity of sperms production in Banana shrimp male broodstock, Penaeus merguiensis fed different natural diets. The three different natural diets namely; squid, fish and shrimp flesh used in this study were obtained from known sources and fed to the tested shrimp in triplicate groups. Based on the results obtained, squid seem to be the most effective natural diet as it enhances the sperms maturation within 20 days. Feeding fish and shrimp flesh as diets for the Banana shrimp broodstock resulted in the observation of maturation in 22 and 24 days, respectively. Similarly, squid diet also recorded the highest (p = 0.002; p < 0.05) sperms count (58.6 to 74.5) as compared to fish diet (44.0 to 61.3) or shrimp diet (28.0 to 42.8). Also, feeding squid diet resulted in a higher percentage of live sperms with ranged between 97.75% to 98.80%. On the other hand, broodstocks fed fish and squid flesh was observed with ranges of between 96% to 97.86% and 92.54% to 96.06%, respectively. It was therefore concluded that squid diet was most effective to improve sperm quality, quantity and maturation period in male broodstock of P. merguiensis. Further study should be carried on the reproductive performance of broodstock fed with squid as diets and it effect on the performances of post larvae obtained.